2011
DOI: 10.1530/joe-11-0172
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplementation reverts central adiposity, leptin, and insulin resistance in adult offspring programed by neonatal nicotine exposure

Abstract: Obesity is a worldwide epidemic. Calcium influences energy metabolism regulation, causing body weight loss. Because maternal nicotine exposure during lactation programs for obesity, hyperleptinemia, insulin resistance (IR), and hypothyroidism, we decided to evaluate the possible effect of dietary calcium supplementation on these endocrine dysfunctions in this experimental model. Osmotic minipumps containing nicotine solution (N: 6 mg/kg per day for 14 days) or saline (C) were s.c. implanted in lactating rats 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Leptin gene expression was quantified as previously described (Nobre et al 2011). Total RNA was isolated from inguinal adipose tissue using a commercial kit (RNeasy lipid tissue mini kit, Qiagen, Hilden Germany).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Leptin gene expression was quantified as previously described (Nobre et al 2011). Total RNA was isolated from inguinal adipose tissue using a commercial kit (RNeasy lipid tissue mini kit, Qiagen, Hilden Germany).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The concentration of calcium used here is twice the amount recommended to rodents (5 g/kg of chow) and is based on the recommendation for calcium supplementation in humans. We previously published that, at this concentration, calcium does not seem to change diet palatability since food intake, body mass, fat depot, serum leptin as well as hypothalamic leptin signaling of lean control rats are not altered by this calcium-rich diet when compared with control animals with no calcium supplementation (Nobre et al 2011(Nobre et al , 2012.…”
Section: Calcium-enriched Dietmentioning
confidence: 82%
“…Previous data from our group have demonstrated that a calcium-supplemented diet is able to decrease visceral adiposity and 25(OH)D levels in two obesity models (early weaning and postnatal nicotine exposure), which can be associated (Nobre et al 2012(Nobre et al , 2016 or not (Nobre et al 2011) with reduction in food intake. These data lend support to the notion that dietary calcium supplementation can have beneficial effects on adipose tissue through changes in GC and vitamin D metabolism and receptors function.…”
Section: :2mentioning
confidence: 88%
“…Offspring in the C group continued to consume standard rat chow until they were 180 days old. Because a previous study found that calcium supplementation had no effect on parameters of interest in control animals , in the present study, the C group's diet was not supplemented with calcium.…”
Section: Methodsmentioning
confidence: 99%